Psychologic Resilience and Related Factors in the Euthymic Bipolar Patients - Ersin Uygun; Aylin Koseoglu; Suat Kucukgoncu; Sahap N. Erkoc (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Bipolar I disorder is characterized by full blown manic episodes and is not only affected by biological factors but also by psychological and cultural factors. This fact attracted the attention onto the psychological resilience, which is the ability of dealing with stressful life-events and overcoming the traumatic experiences, and it has become a phenomenon that is taken into consideration to empower the protective factors for the disorder. The object of this study was to examine social, clinical and physical factors that could enhance the psychological resilience. The subjects of the study were between the ages of 18 and 69, literate and in the phase of euthymic mood. In the study, the 67,4 % of the subjects were women and the average age was 37,7. The scales were Personal Information Form and Psychological Resilience Scale for Adults. It was found that there was a meaningful relationship between attempting to suicide and psychological resilience (p: 0,02 and t: -2,4). When the relationship between being physically active and psychological resilience was examined, it was found that there was a meaningful and a negative correlation between psychological resilience and having a sedentary life style (p: 0,02 and r: -0,35), and between psychological resilience and the time spent in sleep (p: 0,021 and r: -0,35). As a result, resilience is a factor that can be enhanced with different factors and it takes roles both in the process of the disorder to smoothen the course of the disorder and before the symptoms of the disorder appears. [JCBPR 2018; 7(3.000): 120-126]